HIGH PERFORMANCE INFORMATIONAL ENVIRONMENT FOR CALCULATIONS IN BIOMEDICINE - K. S. Brazovsky; Ya. S. Pekker; V. P. Dyomkin; O. S. Umansky; I. V. Tolmachyov (Бюллетень сибирской медицины)
This work represented one of the possible approaches to providing the required computational resources for solving the complex data processing tasks in biomedicine. The proposed solution is based on four tightly interacted key components of modern high performance computational systems: high performance computational cluster, data processing center, specialized data store and protected telecommunication channels. The examples of tasks, which have been solved in the developed information environment, are given.